Pelatihan Pembuatan Blog Pembelajaran Bagi Guru Sekolah Dasar Punna Karya Kabupaten Tangerang - Suntoro (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
The aim of community service is to provide blogging skills that can be utilized by Punna Karya Tangerang elementary school teachers in learning. The service delivery method is a workshop held from November to December 2019. Evaluation of activities is carried out using non-test techniques using questionnaires and documentation. The questionnaire was used to compare teachers' understanding of creating learning blogs between before and after the training was carried out. While the documentation serves to see qualitatively a learning blog created by the teacher. The results of this community service are: (1) classically the competence of teachers in creating learning blogs increased by 85,80%; (2) qualitatively the learning blog produced by the teacher is good, but there are still shortcomings in terms of interface design, navigation, and its contents. Based on these results teachers should be able to improve their skills independently in designing blog-based learning media through online and print references.